Contemporary, mechanism-anchored biomarkers of endothelial dysfunction and oxidative stress (established and emerging) - Skibicka, Katarzyna; Wesołowska, Weronika; Jaśniak, Albert; Bujak, Robert (Journal of Education, Health and Sport, 2025)
Background: Endothelial dysfunction and oxidative stress act together across hypertension, atherosclerosis, coronary disease and heart failure. Loss of nitric oxide (NO) signalling and excess reactive oxygen species (ROS) fuel inflammation, thrombosis and adverse remodelling Objective: To provide a contemporary, mechanism-anchored review of established and emerging biomarkers of endothelial dysfunction and oxidative stress, explain what each marker indicates and how it is measured and outline how small multimarker panels can support risk assessment, therapy monitoring and clinical decisions. Results: Across studies, ADMA, NO/eNOS coupling or FMD, OSE, and hs-CRP/adhesion molecules consistently indicate endothelial activation or impaired vasoprotection. On the oxidative axis, NOX activity, xanthine oxidase/uric acid, ox-LDL/LOX-1, and oxysterols signal lipid oxidation and redox stress within plaques. In practice, compact panels that combine one endothelial, one oxidative and one inflammation marker appear more informative than single tests and may help show target engagement during treatment (e.g., ox-LDL/LOX-1 fall with intensive LDL lowering; urate falls with XO inhibition; FMD and some oxidative footprints improve with lifestyle optimisation). Conclusions: Biomarkers spanning endothelial function and oxidative injury provide actionable signals for earlier risk identification and therapy monitoring. Using small, feasible panels and standardised measurement can make these tools clinically practical, while future trials should link biomarker change to outcomes.